COST MANAGEMENT IN THE COMPETITIVE STRATEGIES OF AGRICULTURAL ENTERPRISES - Yatsiv , І.; Yatsiv , С. (Bulletin of Lviv National Environmental University. Series "AIC Economics", 2024)
The article examines the trends in the formation of production costs in agricultural enterprises of Ukraine in recent years, particularly due to martial law. The proportion of labor and depreciation costs to overall production costs is seen as a good indicator of how agricultural enterprises are responding to market competition. The study has identified specific characteristics in the formation of production costs based on the size of agricultural enterprises. In recent years, small agricultural enterprises have experienced higher growth rates of production costs and payback rates compared to large and medium-sized enterprises. This sheds light on the approaches to cost management at small agricultural enterprises, including microenterprises. The article argues for the importance of implementing a competitive cost minimization strategy for agricultural enterprises. It outlines the content of this strategy, taking into account the particularities of agricultural production. The strategy aims to optimize the volume and structure of costs to ensure high technological efficiency of production and low production costs. The application of the cost minimization strategy as a primary competitive strategy is particularly relevant for medium-sized agricultural enterprises. Furthermore, the article delves into the role of cost management in the functional strategies that enhance the competitiveness of agricultural enterprises. The recommended approach for implementing such strategies is through the execution of an investment project by the enterprise. Cost management involves justifying the estimate, determining the expected efficiency of the project, and exercising control over costs at all stages of its life cycle. It is emphasized that successful cost management in the application of a functional competitive strategy depends on the system of internal economic relations established in an agricultural enterprise.